The Role Of Foreign Direct Investment Inflow And Outflow In India’S Economic Growth (Journal of Informatics Education and Research, 2025)
This study explores the dual role of Foreign Direct Investment (FDI) inflows and outflows in shaping India's economic growth from 2000 to 2022. Employing advanced econometric tools such as Autoregressive (AR) models, Moving Average (MA) Models, Johansen Co-integration, and Granger Causality tests, the research investigates the dynamic interrelationship between FDI trends and economic performance. The analysis confirms a long-term equilibrium between FDI inflows and outflows, with past values significantly predicting future movements, especially in outflows. FDI inflows have fueled sectoral development, employment, and technological advancement, while outflows signify India’s growing global footprint and strategic investments abroad. The Granger Causality test indicates that outflows predict inflows but not vice versa. These findings highlight the importance of FDI as a catalyst for economic development and suggest that a balanced and strategic approach to both inward and outward FDI can enhance India's position in the global economy. The study offers key insights for policymakers and investors alike.